2018
DOI: 10.1080/03014460.2017.1413133
|View full text |Cite
|
Sign up to set email alerts
|

The genetic landscape of Mediterranean North African populations through complete mtDNA sequences

Abstract: The analysis of the complete mtDNA genome has allowed for the identification of a North African sub-lineage that might be ignored by the analysis of partial mtDNA control region sequences, highlighting the phylogeographic relevance of mtDNA complete sequence analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…miR-21, miR-183, miR-182, miR-425-5p and miR-200c were found to be upregulated in tumor versus normal adjacent breast tissues, similar to the Lebanese patients and patients in other studies reported in the literature [20,25]. This study is the first to report the patterns of miRNA dysregulation in the Algerian population, one of North African populations that are known to possess great gene pool heterogeneity from Eurasia, Sub Saharan Africa and North Africa [49]. Furthermore, several meta-analyses report ethnic differences in miRNA deregulations in cancer [50,51].…”
Section: Discussionsupporting
confidence: 83%
“…miR-21, miR-183, miR-182, miR-425-5p and miR-200c were found to be upregulated in tumor versus normal adjacent breast tissues, similar to the Lebanese patients and patients in other studies reported in the literature [20,25]. This study is the first to report the patterns of miRNA dysregulation in the Algerian population, one of North African populations that are known to possess great gene pool heterogeneity from Eurasia, Sub Saharan Africa and North Africa [49]. Furthermore, several meta-analyses report ethnic differences in miRNA deregulations in cancer [50,51].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, mitogenomes and their Hg were successfully determined from 18 modern Ibizans (Table 1 ). A Median Joining network of 111 mitogenomes representing the ancient and modern mitogenomes generated in this study with 83 publicly available ancient mitogenomes from European and Near Eastern 3 , 23 , 29 , 34 36 and modern North African 37 populations is shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the geographical pattern of variation in the shape of the birth canal, we compared the variation in pelvic indices among continents using ANOVA and a post hoc Tukey test. North African (here represented by Egypt) and European populations were analysed together, as movement of people across and around the Mediterranean appears to have been higher than across the Sahara Desert [48,49].…”
Section: (A) Variation In Shape and Sizementioning
confidence: 99%